Perlawanan terhadap Marginalisasi Perempuan dalam Islam: Analisis Wacana Kritis pada Laman mubadalah.id - Amarilisya, SettingsAliftya (Jurnal Komunikasi Islam, 2020)
The growing phenomenon of hijrah lately has been used by many groups to campaign various religious issues. However, the campaign contents are often discriminatory through flouring the logic of gender as natural. This study analyses the discourse of contemporary Muslim women’s resistance to the marginalisation and domestication on mubadalah.id site. Using a qualitative research design and Norman Fairclough’s critical discourse analysis, the results of this study indicate that mubadalah.id considers the discourse of marginalisation of women is contrary to gender equity taught in Islamic teachings. This online media also provides a counter discourse that men are also responsible for domestic works.